MICROSTRUCTURAL CHARACTERISTICS OF THE Longissimus dorsi MUSCLE IN BRAHMAN CROSS CATTLE - Sofyan, Hamny; Jalaluddin, Muhammad; Rahmi, Erdiansyah; Wahyuni, Sri; Hidayat, Taufan; Adam, Mulyadi; Gani, Fadli A; Sabri, Mustafa; Ritonga, Mudhita Zikkrullah (Jurnal Kedokteran Hewan, 2022)
This study aimed to analyze the muscle microstructure of longissimus dorsi Brahman cross (BX) cattle slaughtered at the slaughterhouse of North Aceh District. The meat samples for the study were taken from three male BX cattle aged 18-30 months with body weights ranging from 400 kg to 500 kg and the average body condition scores (BCS) of 3-4. The muscle used was the longissimus dorsi muscle. The mean (SE) diameter and cross-sectional area (CSA) of muscle fibers and the percentage of fast fibers in the longissimus dorsi BX muscle were 71.691.23 m, 4263.43305.69 m2 , and 48.178.81%, respectively. This study concluded that the longissimus dorsi muscle of the BX has relatively large muscle fibers, some of which in each fascicle are composed of fast muscle (fast fiber/type II).